Photopatterning of Azobenzene‐Containing Liquid Crystalline Triblock Copolymers: Light‐Induced Anisotropy and Photostabilization. Issue 20 (13th September 2020) - Audia, Biagio; Bugakov, Miron A.; Boiko, Natalia I.; Pagliusi, Pasquale; Cipparrone, Gabriella; Shibaev, Valery P.
Abstract: Photochromic liquid crystalline block copolymers (PLCBCs) are currently playing a significant role as light‐responsive materials because of their light controllable features over multiple length scales. Herein, a study of the photoinduced optical anisotropy derived by the combination of orientation phenomena at molecular and supramolecular levels in a novel kind of side‐chain PLCBCs with mesogenic phenyl benzoate groups and pyridine units that is hydrogen bonded with azobenzene‐containing phenol is reported. Based on the polymeric architectures and composition, the supramolecular configuration self‐organizes in different microphases that affect the material response to the external stimuli. Simple, 1D, polarization holograms are recorded to evaluate the photoinduced birefringence. The first step, light patterning, involves the orientation of the azobenzene units and precedes a thermal treatment that amplifies the induced anisotropy through the cooperative orientation of the mesogenic units. By selective extraction, the azobenzene units can be removed, making the material transparent to the visible light. Excellent photostability of the material birefringence is obtained, whose final value is strongly affected by the block copolymer's architecture. The versatility in the molecular design, the fine control of the photoinduced features by external parameters, and, finally, the possibility to achieve photostability make these materials of great potential for developing optical and photonic devices. Abstract : The supramolecular architecture of azobenzene‐containing liquid crystalline triblock copolymers is investigated in order to control photoinduced optical properties. The combined approach based on flexible composition of block structures and hydrogen‐bonded photoresponsive units enables to optimize induced optical anisotropy and to acquire excellent photostability of holographically recorded structures, providing an effective strategy to design custom materials for optics and photonics.